Outcome of Closure of Transient Ileostomy at Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: The purpose of our study is to find out the complications of reversal of ileostomy after interval of 3 to 5 months so that patients be called for ileostomy closure at proper time to benefit them with least complications.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at Surgical Department, PMCH Nawabshah from November 2016 to October 2018.Materials and Methods: The patients included in this study were of previously operated for multiple diseases in elective as well as in emergency. After passing from 3 to 5 years duration, they were called on in OPD for admission and planned for reversal of ilesotomy after getting proper investigations and doing appropriate preoperative preparation. Postoperatively, they were assessed for the outcome of its closure for a week in hospital and later on follow-ups.Results: total 50 patients were included in this study. 27(54%) were male and 23(46%) were female. They were previously operated for various pathologies such as typhoid ileal perforation, tuberculous strictures, trauma to samall or large bowel, sigmoid volvulus, cecal perforation and fecal fistulas. In our study, the complications rate was least as compared to othrs. Only 4(8%) patients developed fecal fistula, 5(19%) wound infection, 2(4%) inta- anbdominal abscess, 1(2%) Subcutaneous hematoma, 3(6%) postoperative diarrhea, 2(4%) urinary retention. No expiry was recorded in our study after reversal of temporary ileostomy.Conclusion: in summary, it is concluded that in our study the outcome of ileostomy closure was the best due to appropriate timing established for closure, proper end to end anastomosis and prevention of patient from prolonged paralytic ileus.